POTENSI HIDROSOL SEREH WANGI SEBAGAI SPF (SUN PROTECTION FACTOR) DALAM SEDIAAN LOTION MIKROEMULGEL - Antari, Ester Dwi; Santika Putri, Vania; Asih Winarni, Arum; Syahrul Afianto, Muhammad (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
The inclusion of sunscreen in cosmetic products is widely used globally in the cosmetics industry as it ensures adequate protection against harmful UV rays. This sunscreen product can be packaged into emulsion, cream, gel, and lotion. Cymbopogon nardus hydrosol is a by-product of the distillation of essential oils. This hydrosol is often unused and is simply thrown away, causing new environmental problems. Cymbopogon nardus hydrosol still has the properties of Cymbopogon nardus essential oil as an antioxidant with an IC50 value of 9,322 ppm which is included in the very strong antioxidant category. Cymbopogon nardus hydrosol was made using the water distillation method, then microemulgel lotion was made and physical tests were carried out on the microemulgel lotion. Hydrosol and microemulgel lotion were measured for SPF values. The research results showed that Cymbopogon nardus hydrosol and Cymbopogon nardus microemulgel lotion preparations had SPF values ​​in the ultra category. The higher the SPF value, the better it will protect the skin from the bad effects of UV radiation, one of which is skin cancer. Antioxidants are able to reduce superoxide through the formation of hydroperoxide intermediates so that they can prevent biomolecular damage by free radicals. The microemulgel preparation was stable in the Cycling stability test.